Keunggulan Manajemen Pendidikan Perspektif Rushdi Ahmad Tuaimah - Inayati, Mahfida; Fadholi, Ali Nizar (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
The excellence of investigation management is one of the most important reasons for staying afloat in this time. The concept of excellence in education management according to Rhusdi Ahmad Tuaimah is centered on a goal, principle and also a strategy that aims to improve the administration of education and the educational process both at the national and international levels. This study aims to compare the perspectives of Rusdhi Ahmad Tuaimah with the figures. The research method used is a qualitative approach with a type of library study (library research), the data source used is secondary data and the data analysis technique is content analysis. Thus the excellence of educational management both in administration and the learning process so as to achieve the objectives of the process and strategies contained in educational institutions.